Improving English Learning Outcomes Through Cooperative Learning The Index Card Match Model (Finding A Partner) in Students During The Covid-19 Pandemic - Jannah, Fiqhul (BAHTRA: Pendidikan Bahasa dan Sastra, 2023)
During the Covid-19 pandemic, the English language learning outcomes of Class VII students at SMP Negeri 3 Labuhan Haji for the 2021/2022 academic year were still low. In every assessment carried out, whether in practice or daily tests, the majority of Class VII students are still relatively low. The purpose of this research is to find out whether cooperative learning with the Index Card Match Model can improve English learning outcomes in Procedure Text material for Class VII students at SMP Negeri 3 Labuhan Haji during the Covid-19 Pandemic, Odd Semester of the 2021/2022 Academic Year. The type of research carried out is classroom action research (CAR) and is carried out in the odd semester of the 2021/2022 academic year. This classroom action research was carried out at SMP Negeri 3 Labuhan Haji, which is the researcher's assignment location. This research was carried out using two cycles, with each cycle carrying out a learning process at least 3 meetings including evaluation activities. This research was carried out for approximately three months, namely from September to November 2021.The research subjects were Class VII students of SMP Negeri 3 Labuhan Haji for the 2021/2022 academic year, totaling 27 students.Based onBased on the results of the analysis and, it can be concluded that the application of learning withIndex Card Match Cooperative Learning Modelcan improve the learning outcomes of Class VII students at SMP Negeri 3 Labuhan Haji for the 2021/2022 academic year. This can be seen from the average score obtained by students in cycle I of 68.14 and the average score of students in cycle II of 73.70, which means there is an increase in the learning mastery obtained by students in cycle I of 74.07% to 85.18% in cycle II